1994
DOI: 10.1002/bjs.1800811021
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of recurrent bleeding after endoscopic haemostasis in non-variceal upper gastrointestinal haemorrhage

Abstract: Endoscopic haemostasis by injection of adrenaline was attempted in 135 consecutive patients with active upper gastrointestinal bleeding. Initial haemostasis was obtained in 127 patients following injection of 5-15 ml 1:10,000 adrenaline; eight patients in whom haemostasis was not achieved underwent immediate laparotomy. There was further haemorrhage in 25 patients, which was successfully treated by further injection of adrenaline in ten. Fifteen patients had major rebleeding requiring emergency surgery. Stepwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
10

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 24 publications
3
20
0
10
Order By: Relevance
“…In respect to the diagnosis of gastritis, our diagnostic profile is similar to that found in European studies, but the prevalence of bleeding from varices is greater among our patients (17,22,28) . This finding may be explained by the fact that a quarter of our patients presented previous evidence of portal hypertension, and that in agreement with other studies (19,26) , varices were the most common source of bleeding in such patients.…”
Section: Discussionsupporting
confidence: 93%
“…In respect to the diagnosis of gastritis, our diagnostic profile is similar to that found in European studies, but the prevalence of bleeding from varices is greater among our patients (17,22,28) . This finding may be explained by the fact that a quarter of our patients presented previous evidence of portal hypertension, and that in agreement with other studies (19,26) , varices were the most common source of bleeding in such patients.…”
Section: Discussionsupporting
confidence: 93%
“…In 1987, Provenzale et al [28] tested various predictors of death from gastrointestinal bleeding and found that comorbid factors (i.e., liver and renal disease) and bleeding (i.e., hematochezia, short duration of bleeding, drop in hematocrit of 5% and hypotension) were the most valid. Subsequently, several other risk scoring systems have been developed, with some of them validated in different patient populations [30,37,40,41] . Risk scores have been most commonly used as an aid to clinical decision-making to identify subjects who can be efficiently managed as outpatients, rather than being unnecessarily admitted for a prolonged hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…VDÜGİSK olgularının incelendiği bir çalışmada %33 ile duodenal ülser ilk sırayı, %14 ile gastrik ülser 2. sırayı, %10 ile gastrik erozyon 3. sırayı almıştır (24). Varis dışı üst GİS kanamalar ile ilgili başka bir çalışmada hastaların %33'ünde duodenal ülser, %18'inde gastrik ülser, %4'ünde hem duodenal hem de gastrik ülser, %13'ünde eroziv gastrit, %4'ünde eroziv duodenit, %10'unda eroziv özofajit, %5'inde Mallory-Weiss sendromuna bağlı kanama olduğu saptanmıştır (25). Özen ve arkadaşları (9) yaptıkları benzer bir çalışmada endoskopi yapılmasına rağmen 6 (%1.5) olguda kanama odağı saptanamamış.…”
Section: Forrestunclassified